Reproductive performance and productivity of Menz sheep in the Ethiopian highlands - Mukasa-Mugerwa, E.; Lahlou-Kassi, A. (Elsevier, 1995)
Ewe lambs attain puberty at 10 months and 16.9 + 0.01 kg (56 percent of mature weight) and first lamb at 15 months. Postpartum anoestrus in 76 days, lambing interval is 8.4 months and 65 percent of ewes lamb three times in 2 years with a gestation period of 149 days. Ewes cycle year-round but oestrus activity declines from June to September due to increased silent ovulations. Fertilisation rates are high (greater or equal to 90 percent) but lambing rate is 72 percent, suggesting moderate embryonic mortality. Conception rates to first, second and third oestrus postpartum are 78 percent, 18 percent and 4 percent, respectively. Litter size (prolificacy) is 1.12 but can be increased by 10-40 percent through premating ewe nutrition management or treatment with gonadotropins. Ewe oestrus activity can be synchronised by ram introduction after a period of isolation and with progesterone sponges or prostaglandin F2 alpha therapy. Lambs average 2.0 + 0.1 kg at birth but preweaning mortality (15 percent) and slow growth, resulting in 8.6 kg weaning weight, still limit overall productivity index to 11.0 + 0.87 kg per ewe per year, and the annual reproductive rate to 1.4 lambs per ewe. In the traditional management system, where most animals are raised, further studies are required into better nutrition and control of diseases (endoparasitism) in young animals to increase reproductive efficiency, flock productivity and number of animals for finishing and slaughter. This could serve as a model for interventions in other ruminants in the agroecological zone.